Study of professional education policy in the oriented bahia for social inclusion: methodological explanitation - Silva, Rosemary Lopes Soares da (Universidade Estadual de Campinas, 2019)
Explain the techniques and procedures, the concepts and categories with which the interpretation of the documents related to the Technical Vocational Education Policy of Medium Level -, implemented in Bahia / Brazil, specifically, based on the quadripolar approach that gave the theoretical-methodological density to the study of the object in relation to the epistemological, theoretical, technical and morphological poles. In this perspective, the realization of a research is not the fulfillment of “methodological ritualism” with a “theoretical fad” to avoid repeating what commonly happens in research in education, in a progressively more intense way, of eclectic attempts that randomly join techniques, methods and theoretical references without a clear understanding of the epistemological foundations  of the different paths of knowledge.